Mutation-specific effects of NRAS oncogenes in colorectal cancer cells. (January 2021) - Kuhn, Natalia; Klinger, Bertram; Uhlitz, Florian; Sieber, Anja; Rivera, Maria; Klotz-Noack, Kathleen; Fichtner, Iduna; Hoffmann, Jens; Blüthgen, Nils; Falk, Christine; Sers, Christine; Schäfer, Reinhold
Abstract: In colorectal cancer (CRC), the prevalence of NRAS mutations (5–9%) is inferior to that of KRAS mutations (40–50%). NRAS mutations feature lately during tumour progression and drive resistance to anti-EGFR therapy in KRAS wild-type tumours. To elucidate specific functions of NRAS mutations in CRC, we expressed doxycycline-inducible G12D and Q61K mutations in the CRC cell line Caco-2. A focused phospho-proteome analysis based on the Bio-Plex platform, which interrogated the activity of MAPK, PI3K, mTOR, STAT, p38, JNK and ATF2, did not reveal significant differences between Caco-2 cells expressing NRAS G12D, NRAS Q61K and KRAS G12V . However, phenotypic read-outs were different. The NRAS Q61K mutation promoted anchorage-independent proliferation and tumorigenicity, similar to features driven by canonical KRAS mutations. In contrast, expression of NRAS G12D resulted in reduced proliferation and apoptosis. At the transcriptome level, we saw upregulation of cytokines and chemokines. IL1A, IL11, CXCL8 (IL-8) and CCL20 exhibited enhanced secretion into the culture medium. In addition, RNA sequencing results indicated activation of the IL1-, JAK/STAT-, NFκB- and TNFα signalling pathways. These results form the basis for an NRAS G12D -driven inflammatory phenotype in CRC.